Compromised Dynamic Cerebral Autoregulation in Patients with Epilepsy. (7th February 2018) - Lv, Shan; Guo, Zhen-Ni; Jin, Hang; Sun, Xin; Jia, Meiyan; Ma, Hongyin; Lv, Yudan; Qiu, Quanli; Liu, Jia; Yang, Yi
Abstract : Objective. The aim of this study is to analyze dynamic cerebral autoregulation (dCA) in patients with epilepsy. Methods. One hundred patients with epilepsy and 100 age- and sex-matched healthy controls were recruited. Noninvasive continuous cerebral blood flow velocity of the bilateral middle artery and arterial blood pressure were recorded. Transfer function analyses were used to analyze the autoregulatory parameters (phase difference and gain). Results. The overall phase difference of patients with epilepsy was significantly lower than that of the healthy control group (p = 0.046 ). Furthermore, patients with interictal slow wave had significant lower phase difference than the slow-wave-free patients (p = 0.012 ). There was no difference in overall phase between focal discharges and multifocal discharges in patients with epilepsy. Simultaneously, there was no difference in mean phase between the affected and unaffected hemispheres in patients with unilateral discharges. In particular, interictal slow wave was an independent factor that influenced phase difference in patients with epilepsy (p = 0.016 ). Conclusions. Our study documented that dCA is impaired in patients with epilepsy, especially in those with interictal slow wave. The impairment of dCA occurs irrespective of the discharge location and type. Interictal slow wave is an independent factor to predict impaired dCA in patients with epilepsy. Clinical Trial Identifier . This trial is registered withNCT02775682 .